Burned-out testicular germ cell tumour presenting as acute inferior vena cava syndrome. Issue 11 (17th November 2020) - de Souza, Peter; So, Chun Wah; Batura, Deepak; Gayed, Wade; Vrentzou, Eirini
Abstract : Germ cell tumours (GCT) are the most common testicular neoplasms, seen mainly in young adults. Rarely they can affect extragonadal tissues, either as primary tumours or as metastases, most commonly to retroperitoneal lymph nodes. A 'burned-out' testicular tumour is a metastatic GCT with a relatively occult primary testicular tumour, which has histologically spontaneously regressed. We report a case of a 26-year-old man who presented with an acute history of lower back pain and leg swelling. CT demonstrated a large retroperitoneal soft tissue mass causing right-sided hydronephrosis with inferior vena cava and iliofemoral vein thrombosis. Although clinical examination of the testis was normal, ultrasound imaging of the scrotum identified a burned-out testicular primary. Orchiectomy confirmed the diagnosis and the patient responded well to chemotherapy, with no viable residual tumour on follow-up imaging. However, despite nephrostomy insertion, a dimercaptosuccinic acid (DMSA) scan demonstrated loss of function of the right kidney after treatment.